The Influence of Product Quality, Service Quality, and Store Atmosphere on Shopping Decisions at Warung Uma Manis Penebel Tabanan - Hartini, Ni Made; Antari, Ni Luh Sili (Jurnal Manajemen Pelayanan Hotel, 2024)
Companies must have the right marketing strategy in marketing their products. This study aims to analyze the Effect of Product Quality, Service Quality, and Warung Atmosphere on Purchasing Decisions at Warung Uma Manis Penebel Tabanan. Data collection techniques by conducting surveys and documentation. Sampling using the purposive sampling method, namely consumers who have shopped at least 2 times at Warung Uma Manis Penebel Tabanan with an age range of 17-70 years and a sample of 100 respondents. The variables used are product quality variables (X1) and service quality (X2), and store atmosphere (X3) and purchase decision variables (Y). The research method uses multiple linear regression analysis, namely the t test with the help of SPSS version 24 for windows. Based on the results of the study, the regression equation obtained Y = 8.571 + 0.136 X1 + 0.151X2 + 0.338X3. A hypothetical decision was obtained stating that partially the variables of product quality, service quality, and stall atmosphere had a positive and significant effect on purchasing decisions at Warung Uma Manis Penebel Tabanan. Keywords: Product Quality (X1), Service Quality (X2), Store Atmosphere (X3), Purchasing Decision (Y).